Psoriasis in Iceland and symptoms of psychological comorbidities - Dávur Í Dali 1989- (2020)
Psoriasis is an autoimmune inflammatory disease associated with high rates of psychological comorbidities. We hypothesized that there is, as in other countries, a high prevalence of psychological co-morbidities among people who have psoriasis in Iceland. We also hypothesized that these psychological comorbidities very rarely get assessed by healthcare professionals. In this study, we tested these hypotheses and explored qualitatively how psoriasis might affect people’s lives negatively in ways related to behaviors and cognitions. We used a cross-sectional study design, carried out in two parts: A quantitative part using a survey, and a qualitative part using semi-structured interviews. We measured symptoms of anxiety, depression, health anxiety, and functional impairment in a survey containing the General Anxiety Disorder-7 scale (GAD- 7), the Patient Health Questionnaire-9 (PHQ-9), the Short Health Anxiety Inventory (SHAI), and the Work and Social Adjustment Scale (WSAS). Participants were made aware of the survey through the Icelandic psoriasis and eczema association’s (SPOEX) website and related Facebook groups. We assessed how psoriasis affects people’s lives negatively using thematic analysis of semi-structured interviews. The results showed, in support of our hypotheses, that 65% of our participants (N = 123) had clinically significant symptoms of psychological comorbidity, 22% participants reported suicidal ideations, and 84% had never been asked about their mental health in relation to their psoriasis by a healthcare professional. We identified six themes in the thematic analysis. Our results clearly show that more attention needs to be directed at this population's psychological needs.